Adopting digital transformation in small and medium enterprises: An empirical model of Influencing factorsbased on TOE-TAM integrated - Nguyen, Xuan Truong (Journal of Finance - Marketing Research, 2022)
This study examined relations between factors impacting the adoption of digital transformation of small and medium enterprises (SMEs) in the Vietnam context by mixed method research. The qualitative research was carried out by a group discussion with 11 participants and a cross-sectional survey with 346 valid questionnaires. The results show the relative advantage, perceived benefits of digital transformation, compatibility, security concern, competitive pressure, vendor support, top management support, investment readiness, perceived usefulness, and attitudes toward adoption have impacted the adoption of digital transformation in SMEs in Vietnam. This research contributed to extending the academic framework and examining causal relationships by adopting new characteristics from the integrated perspective of TOE with TAM beyond the existing research models. The findings are the basis for the government to propose policies to promote digital transformation and for SMEs to prepare technological and organizational readiness for successful digital change.